IL‐27 enhances LPS‐induced IL‐1β in human monocytes and murine macrophages. Issue 1 (4th April 2017) - Petes, Carlene; Wynick, Christopher; Guzzo, Christina; Mehta, Divya; Logan, Sarah; Banfield, Bruce W.; Basta, Sameh; Cooper, Andrea; Gee, Katrina
Abstract : A previously undefined role for IL‐27 in the optimal production of caspase‐1‐ and P2X7‐dependent LPS‐induced IL‐1β production in monocytic cells. Abstract : IL‐27 bridges innate and adaptive immunity by modulating cytokine production from myeloid cells and regulating Th cell differentiation. During bacterial infection, TLR4 triggering by LPS induces IL‐27 production by monocytes and macrophages. We have previously shown that IL‐27 can prime monocytes for LPS responsiveness by enhancing TLR4 expression and intracellular signaling. If unregulated, this could result in damaging inflammation, whereas on the other hand, this may also provide greater responses by inflammatory processes induced in response to bacterial pathogens. A key process in fine‐tuning inflammatory responses is activation of the inflammasome, which ultimately results in IL‐1β production. Herein, we investigated the molecular mechanisms by which IL‐27 modulates LPS‐induced IL‐1β secretion in monocytes and macrophages. We found that when delivered simultaneously with LPS, IL‐27 augments activation of caspase‐1 and subsequent release of IL‐1β. Furthermore, we determined that IL‐27 primes cells for enhanced IL‐1β production by up‐regulating surface expression of TLR4 and P2X purinoceptor 7 (P2X7) for enhanced LPS and ATP signaling, respectively. These findings provide new evidence that IL‐27 plays an important role in the proinflammatory capacity of monocytes and macrophages via enhancing IL‐1β secretion levels triggered by dual LPS–ATP stimulation.